Tax Planning as a Strategic Catalyst: Moderating the Relationship Between Current Tax Expense and Earnings Management - Bukhori Muslim, Ahmad; Oktaviano, Benny; Triwibowo, Edi (Journal of Applied Accounting and Taxation, 2026)
Growing concerns over aggressive earnings management practices have raised questions about the role of tax planning in corporate reporting. This study aims to examine whether tax planning moderates the relationship between current tax expense and earnings management in publicly listed manufacturing companies. Using panel data from firms listed on the Indonesia Stock Exchange during 2019–2023, the analysis employs regression models with interaction terms to capture the moderating effect. The results indicate that tax planning significantly alters the relationship, allowing firms to manage earnings without proportionally increasing current tax expenses. These findings highlight the dual role of tax planning as both a tool for fiscal efficiency and a potential mechanism for opportunistic behavior. The study concludes that stricter oversight is necessary to ensure that tax planning practices do not undermine the integrity of financial reporting.